Radiation Effects and Service Function of Aquatic Ecosystem - Xu Jinpeng; Xu Yingjun; Meng Yu; Shi Jifeng; Guan Xinjian (Shuitu baochi tongbao)
[Objective] The value change and radiation effect of the regional aquatic ecosystem service function were analyzed in order to provide a scientific basis for sustainable development of regional water resources and ecological compensation of a river basin. [Methods] ArcGIS software was used to extract land use data for Luoyang City, Henan Province from 2000 to 2020 in order to obtain the area of water type. The emergy method was used to quantify and analyze the changes of aquatic ecosystem service functions, and the functional radiation was analyzed by the break point model. [Results] From 2000 to 2020 (in five-year time steps), the total emergy values of aquatic ecosystem services at Luoyang City were 8.01×1021 sej， 1.29×1022 sej， 1.27×1022 sej， 1.29×1022 sej， and 1.31×1022 sej, respectively, with a general increasing trend. Among these emergy values, the focus of service composition had shifted from supply function to cultural function. In this system, biodiversity protection, aquatic product production, water resource supply, water resource regulation, and leisure and entertainment functions were dominant. Leisure and entertainment functions have become core functions. In addition, the main transfer areas of the aquatic ecosystem service function in Luoyang City were Songxian County and Luoning County, with total outward transfer values of 3.10×1020 sej and 3.21×1020 sej, respectively. The main transfer areas were Luanchuan County, Yiyang County, Yichuan County, and Ruyang County. [Conclusion] Greater attention will need to be given to ecological protection of water, increasing support and guidance for regional tourism, and reasonably carrying out ecological compensation in areas similar to Luoyang City to promote the coordinated development of the economy, society, and ecology in various regions.